Health-benefitting Biologically Active Substances in Edible Apricot Flowers - Martina Göttingerová; Michal Kumšta; Tomáš Nečas (HortScience, 2020)
The nutritive quality of food and the aesthetic aspect contribute to the appearance of consumed food. In this study, apricot (Prunus armeniaca L.) flowers were used to determine vitamin C, total phenolic content, flavonoids, antioxidant capacity, carotenoids, anthocyanins, and amygdalin. Vitamin C content fluctuated between 24.97 and 47.35 mg·100 g–1 fresh weight (FW). The results show that all apricot flowers are a good source of phenolic compounds [404.08–768.45 mg gallic acid equivalent (GAE)/100 g FW] and flavonoids [198.76–538.11 mg catechin equivalent (CE)/100 g FW], and have good antioxidant capacity [414.66–1026.18 mg Trolox equivalent (TE)/100 g FW]. A high value of anthocyanins was measured in ‘Vestar’ (28.41 mg·100 g–1 FW) and also in ‘Blenheim’ (13.40 mg·100 g–1 FW). On the contrary, a low value was found in ‘Scout’ (1.60 mg·100 g–1 FW). The highest value of carotenoids was measured in ‘Blenheim’ (6.41 mg·100 g–1 FW), and the lowest in ‘Chuang Zhi Hong’ (1.36 mg·100 g–1 FW). Amygdalin content fluctuated between 110.81 and 419.78 mg·100 g–1 FW. Newly acquired information about the composition and nutritional value of edible flowers give reasons for their consumption.